Immunological aspects of halo nevus (Sutton’s Nevus) - Hlača, Nika; Vičić, Marijana; Prpić-Massari, Larisa (Frontiers in Immunology, 2026)
Halo nevus has historically been observed as a localized skin phenomenon surrounding a melanocytic nevus. However, emerging studies indicate that halo nevus serves as a model for immune-mediated, primarily CD8+ T cells–targeted destruction of melanocytes, similar to vitiligo or regressing melanoma. The aim of this mini-review is to summarize the current understanding of the immunological mechanisms underlying halo nevus formation, to highlight similarities and differences between halo nevus and vitiligo, as well as contrasts with regressing melanoma. Acknowledging halo nevus as a model for a controlled immune response against melanocytes could offer valuable insights into understanding triggers, potential antigens, and the balance of effector and regulatory responses, with translational relevance to pigment disorders and tumor immunology.